The problem of evil - Speak, Daniel (Key concepts in philosophy series (Polity Press), 2015)
"The most forceful philosophical objections to belief in God arise from the existence of evil. Bad things happen in the world and it is not clear how this is compatible with the existence of an all-powerful and perfectly loving being. Unsurprisingly then, philosophers have formulated powerful arguments for atheism based on the existence of apparently unjustified suffering. These arguments give expression to what we call the problem of evil. This volume is an engaging introduction to the philosophical problem of evil. Daniel Speak provides a clear overview of the main lines of reasoning in this debate and argues for the defensibility of theistic belief in the face of evil. He fleshes out the distinction between theodicy and defense and guides the reader through the logical, evidential, and hiddenness versions of the problem."--Publisher's description.